(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2020)
Emulsifier-free, particle-stabilised emulsions called Pickering emulsions of fluconazole for topical delivery, were studied using Taguchi L9 orthogonal array (OA) design. Formulations were prepared by homogenization method, using bentonite in the concentration range of 2-4% w/v, oil phase (coconut oil, oleic acid, sesame oil). In Taguchi L9 OA experimental design, independent variables (oil phase & concentration of bentonite) effect on dependent variables (drug content & release rate) was studied. All the formulations have shown good physicochemical properties. The PS3 formulation containing sesame oil and 4% bentonite was optimized as particle size was found to be 758.0 nm, zeta potential -48 mv, with Q8 of 166.70±0.15μg/cm2, flux of 17.33±0.02 μg/cm2/hr, permeability coefficient of 3.46±0.015 cm/hr×10-3 and skin content of 4.01±0.24 mg/g. The formulations were stable and non-irritant. Hence pickering emulsion of fluconazole using sesame oil can be used for topical delivery as the drug release was maintained at the localised site. Dhaka Univ. J. Pharm. Sci. 19(2): 169-178, 2020 (December)